Canine indolent and aggressive lymphoma: clinical spectrum with histologic correlation. (20th June 2013) - Aresu, L.; Martini, V.; Rossi, F.; Vignoli, M.; Sampaolo, M.; Aricò, A.; Laganga, P.; Pierini, A.; Frayssinet, P.; Mantovani, R.; Marconato, L.
Abstract Sixty‐three dogs with newly diagnosed lymphoma underwent complete staging and received the same chemotherapy. Diffuse large B‐cell lymphoma was the leading histotype (44.4%), followed by peripheral T‐cell lymphoma (20.6%). Indolent lymphomas accounted for 30.2% of cases. Most dogs with aggressive B‐cell lymphoma had stage IV disease. Dogs with indolent and aggressive T‐cell lymphoma had more often stage V disease and were symptomatic. Liver and bone marrow were predominantly involved in B‐cell and T‐cell lymphoma, respectively. The clinical stage was significantly related to substage, sex and total lactic dehydrogenase (LDH) levels. Aggressive B‐cell lymphomas were more likely to achieve remission. Median survival was 55 days for aggressive and indolent T‐cell lymphoma, 200 and 256 days for indolent and aggressive B‐cell lymphoma, respectively. The prognosis of advanced indolent lymphoma does not appear to be appreciably different from that of aggressive disease. Familiarity with the various histotypes is critical to make the correct diagnosis and drive therapy.